Prenatal Exposure to Bisphenol A, E, and S Induces Transgenerational Effects on Female Reproductive Functions in Mice. (27th May 2019) - Shi, Mingxin; Whorton, Allison E; Sekulovski, Nikola; MacLean, James A; Hayashi, Kanako
Abstract: This study was performed to examine the transgenerational effects of bisphenol (BP) A analogs, BPE, and BPS on female reproductive functions using mice as a model. CD-1 mice (F0) were orally exposed to control treatment (corn oil), BPA, BPE, or BPS (0.5 or 50 µg/kg/day) from gestational day 7 (the presence of vaginal plug = 1) to birth. Mice from F1 and F2 offspring were used to generate F3 females. Prenatal exposure to BPA, BPE, and BPS accelerated the onset of puberty and exhibited abnormal estrous cyclicity in F3 females, and those females exhibited mating difficulties starting at 6 months of age. Various fertility problems including reduced pregnancy rates, parturition, and nursing issues were also observed starting at 6 months, which worsened at 9 months. The levels of serum estradiol-17β were elevated by BPA or BPS exposure at the age of 6 months, whereas testosterone levels were not affected. The dysregulated expression of steroidogenic enzymes was observed in the ovary at 3 or 6 months of age by BPE or BPS exposure. However, BPA, BPE, and BPS exposure did not affect neonatal follicular development such as germ cell nest breakdown or follicle numbers in the ovary on postnatal day 4. These results suggest that prenatal exposure to BPA analogs, BPE and BPS, have transgenerational effects on female reproductive functions in mice.